Pemberdayaan Kelompok Tani Peternak Melalui Introduksi Mesin di Dusun Sukamaju Kab. Sumedang - Haryadi, Haryadi; Mahmudi, Ali; Raharjo, Parno; Pamungkas, Adi; Suryadi, Aris; Triyono, Budi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Sukamaju Hamlet, Sukawangi Village, Pamulihan District, Sumedang Regency, is one of the hamlet that still need guidance. Most of the residents are farmers and breeders. The livestocks mostly are sheep, dairy cattle and beef cattle. The hamlet comunity formed a farmer group, called Tunas Muda. This farmer group has various interrelated problems. Economic problems is the lack of capital. Meanwhile, the problem with infrastructure is that there is no processing machine, and no common location. The problem with management is that they do not have a good organization yet. Meanwhile, problems in marketing are the absence of featured products, and the bargaining power of farmers is very low. Through this community service program, in accordance with the fields of expertise and available resources, a chopper machine has been introduced to the Farmer Group to break the chain of problems. The direct result of this introduction is a decrease of fresh forage feed need by 35%. Meanwhile, another result of this program is the strengthening of management in the form of reorganization to strengthen the management, the preparation of a new division of tasks, as well as the construction of a common cage with a capacity of 20 sheep. With the existence of this common cage, it is hoped that it will improve organizational functions, as well as management efficiency and effectiveness. For the sustainability of this program, continuous evaluation and assistance is needed. The strengthening of organizational and financial management has been able to improve marketing. If last year's qurban season, the farmers group could sell 9 heads, this year's qurbani season could sell 15.